2004
DOI: 10.1248/bpb.27.1604
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis by Saussurea lappa and Pharbitis nil on AGS Gastric Cancer Cells

Abstract: We performed this study to understand the molecular basis underlying the antitumor effects of Saussurea lappa, Pharbitis nil, Plantago asiatica and Taraxacum mongolicum, which have been used for herbal medicinal treatments against cancers in East Asia. We analyzed the effects of these medicinal herbs on proliferation and on expression of cell growth/apoptosis related molecules, with using an AGS gastric cancer cell line. The treatments of Saussurea lappa and Pharbitis nil dramatically reduced cell viabilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 24 publications
2
30
0
3
Order By: Relevance
“…Recent scientific efforts have focused on the potential roles of traditional herbs extracts as alternative and complementary medications for cancer treatment (Kim et al, 2012;Lee et al, 2010;Moon, 2012). Currently, Compelling evidence reported by several investigators suggested different anticancer activities of S. lappa extract in both in vitro and in vivo (Ko et al, 2004(Ko et al, , 2005Sun et al, 2003). However, the effect of the S. lappa extract on the growth of KB human oral cancer cell has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent scientific efforts have focused on the potential roles of traditional herbs extracts as alternative and complementary medications for cancer treatment (Kim et al, 2012;Lee et al, 2010;Moon, 2012). Currently, Compelling evidence reported by several investigators suggested different anticancer activities of S. lappa extract in both in vitro and in vivo (Ko et al, 2004(Ko et al, , 2005Sun et al, 2003). However, the effect of the S. lappa extract on the growth of KB human oral cancer cell has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The essential oil of the roots has strong antiseptic, disinfectant and anti-inflammatory properties (Madhavi et al, 2001). Previous study has shown that the ethanol extract of S. lappa has anticancer activity (Ko et al, 2004) in AGS gastric cancer cells. Recently, studies reported that the methanol extract of Gracilaria tenuistipitata (Yeh et al, 2012) and the hexane extract of Rheum undulatum L inhibited oral cancer cell proliferation through apoptosis and the down-regulation of specificity protein 1 and surviving (Choi et al, 2011), respectively.…”
Section: Introductionmentioning
confidence: 95%
“…한방에서 민들레는 포공영이라고 하며 청열해독(淸熱解毒), 소염, 이뇨의 목적으로 이용하여 왔으며 15) , 어린잎은 나물로 뿌리는 약용으로 쓰기도 하였다 16) . 이 밖에도, 항암효과 17) , 위장관의 화생(metaplasia)와 비정형증식증(atypical hyperplasia)의 치료효과 18) , 만성 B형간염의 치료효과 19) , 만 성대장염 20) , 아토피성 피부염 21) , 항 바이러스작용 22) , 요로결 석 2) RAPD PCR 분석 Table 1에 제시하였다. …”
Section: 서 론 1)2)unclassified
“…Previous phytochemical and bioactivity investigations of several species of Saussurea by other scientists in the world have revealed the presence of interesting bioactive compounds like flavonoids (Jiang et al 1979;Fan & Yoe 2003), lignans (Takasaki et al 2000;Ko et al 2004), sesquiterpene lactones (Todorova et al 1991;Yang et al 2004) and γ-linolenic acid (Tsevegsuren et al 1997) with antioxidant, anticancer and anti-atherosclerotic activities.…”
Section: Introductionmentioning
confidence: 99%